Government Ideology and Economic Policy-Making in the United States - Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper describes the role of government ideology on economic policy-making in the United States. I consider studies using data for the national, state and local level and elaborate on checks and balances, especially divided government, measurement of government ideology and empirical strategies to identify causal effects. Many studies conclude that parties do matter in the United States. Democratic presidents generate, for example, higher economic growth than Republican presidents, but these studies using data for the national level do not derive causal effects. Ideology-induced policies are prevalent at the state level: Democratic governors implement somewhat more expansionary and liberal policies than Republican governors. At the local level, government ideology hardly influences economic policymaking. How increasing political polarization and demographic change will influence the role of government ideology on economic policy-making will be an important issue for future research.
Keywords: D72; E60; H00; N12; N42; P16; 330; government ideology; economic policy-making; partisan politics; United States; Democrats; Republicans; political polarization; causal effects